2003
DOI: 10.1002/jbm.a.20034
|View full text |Cite
|
Sign up to set email alerts
|

Performance of hydroxyapatite bone repair scaffolds created via three‐dimensional fabrication techniques

Abstract: The current study analyzes the in vivo performance of porous sintered hydroxyapatite (HA) bone repair scaffolds fabricated using the TheriForm solid freeform fabrication process. Porous HA scaffolds with engineered macroscopic channels had a significantly higher percentage of new bone area compared with porous HA scaffolds without channels in a rabbit calvarial defect model at an 8-week time point. An unexpected finding was the unusually large amount of new bone within the base material structure, which contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(37 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…Biodegradable and bioresorbable polymeric and composite scaffolds with defined internal structures have been manufactured directly as well as indirectly using stereolithography (SLA),3 fused deposition modeling,4 3D plotting,5, 6 and 3D printing 7–10. Ceramic scaffolds for bone replacement have been produced using laminated object manufacturing,11 selective laser sintering,12 SLA,13 and 3D printing 14. Furthermore, wax molds generated by the ModelMaker II RP system (Solidscape Inc., USA) were also used to fabricate ceramic15 and composite scaffolds 16…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable and bioresorbable polymeric and composite scaffolds with defined internal structures have been manufactured directly as well as indirectly using stereolithography (SLA),3 fused deposition modeling,4 3D plotting,5, 6 and 3D printing 7–10. Ceramic scaffolds for bone replacement have been produced using laminated object manufacturing,11 selective laser sintering,12 SLA,13 and 3D printing 14. Furthermore, wax molds generated by the ModelMaker II RP system (Solidscape Inc., USA) were also used to fabricate ceramic15 and composite scaffolds 16…”
Section: Introductionmentioning
confidence: 99%
“…Some studies demonstrated that cell distribution within the TEBG directly influenced and even decided the distribution and growth pattern of bone regeneration [44], [45]. Well-defined 3D scaffold loaded with homogeneous osteoblasts and extracellular matrix promote discontinuous ingrowth with separated bone islands throughout the whole scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…This enables control over various properties, such as thermal and electrical conductivity, hardness, magnetic properties, etc. It is very difficult to make fibre-reinforced composite using a powder-fibre mixture or jetting the fibre, but it is possible to infiltrate a porous preform of ceramics or metal obtained by 3DP with a metal or alloy to make the composite [12][13][14].…”
Section: Three-dimensional Printing (3dp)mentioning
confidence: 99%